A hybrid MCDM approach for evaluating an automobile purchase model. (1st January 2013) - Sakthivel, G.; Ilangkumaran, M.; Nagarajan, G.; Raja, A.; Ragunadhan, P.M.; Prakash, J.
This paper describes an application of hybrid multi criteria decision making (MCDM) technique for the selection of the best car. This study focuses on five alternatives and evaluation criteria such as safety, performance, economic aspect, exterior, convenience, dealer, warranty and emissions to select the best car. Two models are proposed to evaluate the best car. The first model, fuzzy analytical hierarchy process (FAHP) is integrated with Preference Ranking Organization METHod for Enrichment Evaluation (PROMETHEE) technique. The second model, FAHP is integrated with hierarchy grey relation analysis (GRA) technique. Here, the FAHP is used to analyse the structure of car selection problem and to determine the weights of the criteria. The hierarchical GRA and PROMETHEE techniques are used to obtain the final ranking of the cars.